2015
DOI: 10.1016/j.ydbio.2014.08.035
|View full text |Cite
|
Sign up to set email alerts
|

Extraocular muscle satellite cells are high performance myo-engines retaining efficient regenerative capacity in dystrophin deficiency

Abstract: Extraocular muscles (EOMs) are highly specialized skeletal muscles that originate from the head mesoderm and control eye movements. EOMs are uniquely spared in Duchenne muscular dystrophy and animal models of dystrophin deficiency. Specific traits of myogenic progenitors may be determinants of this preferential sparing, but very little is known about the myogenic cells in this muscle group. While satellite cells (SCs) have long been recognized as the main source of myogenic cells in adult muscle, most of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
90
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(102 citation statements)
references
References 104 publications
(186 reference statements)
11
90
1
Order By: Relevance
“…the extraocular muscles) 24 . It has been clearly demonstrated that head and limb muscles possess highly different properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…the extraocular muscles) 24 . It has been clearly demonstrated that head and limb muscles possess highly different properties.…”
Section: Discussionmentioning
confidence: 99%
“…Masseter muscle from old animals seems to retain their regenerative capacity in comparison with limb muscles 25,26 . SCs from the extraocular muscles possess a robust proliferation and differentiation capacity comparable to SCs from head muscles, and show a larger engraftment potential than limb muscle SCs 24 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here too it should be noted that the vast majority of studies on muscle regeneration are performed on the TA muscle. Given the genetic and phenotypic differences between muscles in different anatomical locations (Sambasivan et al, 2009), including the superior engraftment potential of extraocular derived 8 satellite cells compared to those from the TA muscle (Stuelsatz et al, 2015), careful consideration needs to be given to other muscle groups.…”
Section: Morel Et Al 2007)mentioning
confidence: 99%
“…Here too it should be noted that the vast majority of studies on muscle regeneration are performed on the TA muscle. Given the genetic and phenotypic differences between muscles in different anatomical locations (Sambasivan et al, 2009), including the superior engraftment potential of extraocular derived 8 satellite cells compared to those from the TA muscle (Stuelsatz et al, 2015), careful consideration needs to be given to other muscle groups.The most commonly used acute injury models involve intramuscular injection of myotoxins (Cardiotoxin (CTX) and Notexin (NTX)), Barium chloride (BaCl 2 ), and mechanical injury (freeze, needle or crush injuries) Hardy et al, 2016) (Figure 1). …”
mentioning
confidence: 99%